2023
DOI: 10.3390/ma16196373
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Impact of Using FRP Sheets on the Axial Compressive Performance of Short-Circular Composite Columns

Jie Liu,
Deliang Ma,
Feifei Dong
et al.

Abstract: This paper conducts an experimental study on the axial compressive performance of FRP-steel-concrete composite columns. Nine short columns were produced and evaluated in the study, comprising of three concrete-filled steel tube reference columns and six FRP-steel-concrete composite columns, respectively denoted as “reference columns” and “composite columns”. Two categories of failure modes, including shear failure and waist drum, were observed from the experiments. The failure mode may trend toward waist drum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…However, shear failure can still be observed in some cases for the CFST and T-C columns, even with RC or SRC infilling [ 13 ]. Besides, external confinement is employed in the form of steel tubes [ 14 , 15 , 16 , 17 , 18 ], fiber reinforced plastic (FRP) tubes [ 19 , 20 ], FRP jackets [ 21 , 22 , 23 , 24 ], FRP rings [ 25 , 26 , 27 , 28 ], or discrete stirrup [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ], which enhances the mechanical properties of the CFST columns to a certain extent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, shear failure can still be observed in some cases for the CFST and T-C columns, even with RC or SRC infilling [ 13 ]. Besides, external confinement is employed in the form of steel tubes [ 14 , 15 , 16 , 17 , 18 ], fiber reinforced plastic (FRP) tubes [ 19 , 20 ], FRP jackets [ 21 , 22 , 23 , 24 ], FRP rings [ 25 , 26 , 27 , 28 ], or discrete stirrup [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ], which enhances the mechanical properties of the CFST columns to a certain extent.…”
Section: Introductionmentioning
confidence: 99%
“…Materials 2024, 17, x FOR PEER REVIEW 2 of 28 with RC or SRC infilling [13]. Besides, external confinement is employed in the form of steel tubes [14][15][16][17][18], fiber reinforced plastic (FRP) tubes [19,20], FRP jackets [21][22][23][24], FRP rings [25][26][27][28], or discrete stirrup [29][30][31][32][33][34][35][36], which enhances the mechanical properties of the CFST columns to a certain extent. Apart from that, the newly developed steel-tube-confined CFST (T-CFST) columns have been proven to be effective in improving load-bearing capacity and preventing CFST columns from experiencing shear failure [13,37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [152] demonstrated the cracking propagation in small-sized concrete specimens. The development of load-bearing capacity is a significant concern after wrapping FRP cloth around concrete elements [153][154][155]. Campione [156] conducted compressive experiments on concrete prisms wrapped with carbon FRP cloth.…”
Section: Other Frp Application In Concrete Repairmentioning
confidence: 99%
“…Currently, there are various combinations of concrete-filled FRP tube (CFFT) columns that have been studied. Cao et al derived a stress-strain model for FRP-constrained rubberconcrete columns considering the cross-sectional shape through theoretical derivation [11], and Liu et al carried out an experimental study on the axial compression performance of FRP-steel-concrete composite columns, and two types of failure modes were observed [12]. Fang et al proposed a design using recycled aggregate concrete-filled glass fiber-reinforced polymer-steel composite tube columns.…”
Section: Introductionmentioning
confidence: 99%